Results of Minimally Invasive Bipolar Tenotomy of Congenital Muscular Torticollis - Sahu, Ramji Lal (Revista Chilena de Ortopedia y Traumatología, 2019)
Background Congenital muscular torticollis is the postural deformity of the head and of the neck. The purpose of the present study is to evaluate the results of bipolar sternocleidomastoid (SCM) muscle tenotomy in children.Methods The present prospective study was conducted at the Department of Orthopedic Surgery from December 2010 to December 2014. A total of 34 children with congenital muscular torticollis and a mean age of 4.8 years (range: 1–14 years) were recruited from the Outpatient Department. They were treated with bipolar SCM muscle release under general anesthesia. The functional and cosmetic results were rated on a scoring system modified from Lim et al (2014). All of the children were followed-up for 2 years.Results At the final follow-up, the neck range of movement and head tilt improved and their appearance were cosmetically improved despite the long-standing nature of the deformity. The results were excellent in 30 patients (88.23%) and good in 4 patients (11.76%). No postoperative complications were found in any of the 34 patients.Conclusion Bipolar tenotomy of the SCM muscle is a good method for correcting difficult cases of congenital muscular torticollis. It is a safe, effective and complication-free method for these patients.
Keywords: torticollis; bipolar tenotomy; deformity; children